Hubungan Beban Kerja Mental dan Faktor Individu terhadap Stres Kerja selama Pandemi COVID-19 pada Perawat RSUD dr. Dradjat Prawiranegara Kabupaten Serang Tahun 2021 - Maulvi Nurunnisa Adriansyah (2021)
Nurses are one of the health workers who are responsible for handling COVID-19 at this time. The increasing number of COVID-19 cases has put health systems under intense pressure. Work stress might be exacerbated by the possibility of excessive workloads and the risk of viral exposure when treating COVID-19 patients. The purpose of this study is to analyze the association between mental workload and individual factors with the incidence of work stress in nurses on COVID-19 ward of RSUD dr. Dradjat Prawiranegara during COVID-19 pandemic. This study is a quantitative study with a cross-sectional design. Data was collected using General Health Questionnaire-12 (GHQ-12) and National Aeronautics and Space Administration Task Load Index (NASA-TLX). The sampling technique used in this study was total sampling with a sample size of 91 people. The results of chi-square test indicate that there is an association between mental workload and the incidence of work stress (p value 0.039), while there is no association between individual factors such as age (p value 0.132), gender (p value 0.939), work experience (p value 0.213), and marital status (p value 0.472) with the incidence of work stress. Suggestions for hospital to pay attention to work-related stressors by managing stress and providing medical protective equipment to decrease the possibility of infection in COVID-19 ward nurses.